2018
DOI: 10.1186/s12887-018-1076-0
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive breastfeeding practice during first six months of an infant’s life in Bangladesh: a country based cross-sectional study

Abstract: BackgroundBreastfeeding offers incredible health benefits to both child and mother. It is suggested by World Health Organization that an able mother should practice and maintain exclusive breastfeeding for first six months of her infant’s life. The objective of this study was to determine the prevalence and factors associated with exclusive breastfeeding for first six months of an infant’s life in Bangladesh.MethodsData was extracted from Bangladesh Demographic and Health Survey (BDHS-2014). BDHS-2014 collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
86
7
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(132 citation statements)
references
References 38 publications
33
86
7
6
Order By: Relevance
“…Furthermore, this study revealed that mothers with higher levels of education were signi cantly associated reduced levels of EBF practice in both urban and rural areas. This agrees with earlier literature, as mothers with lower levels of education are more likely to breastfeed their infants exclusively than those with higher levels of education [22][23][24][25][26][27][28][29][30]. This may be attributed to the fact that mothers with higher levels of education are likely to be engaged in the formal employment sector, which does not avail them with ample time and strength to adopt EBF practice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, this study revealed that mothers with higher levels of education were signi cantly associated reduced levels of EBF practice in both urban and rural areas. This agrees with earlier literature, as mothers with lower levels of education are more likely to breastfeed their infants exclusively than those with higher levels of education [22][23][24][25][26][27][28][29][30]. This may be attributed to the fact that mothers with higher levels of education are likely to be engaged in the formal employment sector, which does not avail them with ample time and strength to adopt EBF practice.…”
Section: Discussionsupporting
confidence: 90%
“…Maternal education had also been identi ed as relevant and related to knowledge of EBF. In this context, mothers with lower education are more likely to breastfeed their infants exclusively than those with higher education [30], while a study revealed no signi cant relationship between level of education and the practice of EBF [31]. Another study reported that mothers with higher level of education were more likely to breastfeed exclusively for 6months [25], while [22] reported that mothers with at least primary education engaged in early initiation of breastfeeding compared to mothers with no schooling, while those with no formal education had higher odds of not practicing EBF compared to those with secondary education or higher.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal job status is variable that has been associated with breastfeeding. Previous studies 14,18,24 revealed that full-time houseswives have higher breastfeeding rates than mothers with work and the shorter the time to return to work after childbirth, the shorter the breastfeeding period. It is estimated that they stop breastfeeding because they have less time to care for the child while working.…”
Section: Discussionmentioning
confidence: 98%
“…14,15 However, several previous reports showed that the older the mothers were more likely to breastfeed than were younger mothers. [16][17][18] Oakely et al 19 reported that the younger the mother was, the less likely she was to breastfeed or to stop breastfeeding within 6 weeks. We posit that younger mothers lack knowledge and awareness of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation